Perlindungan Hukum Bagi Pekerja Perempuan Hamil Yang Bekerja Lembur Tanpa Upah Lembur (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2023)
This research was prepared with the title "Legal Protection for Pregnant Women Workers Who Work Overtime Without Overtime Pay." The research method used is normative juridical, using a conceptual approach and a statutory approach. The formulation of the problem in this study is how is legal protection for pregnant women workers who do not get overtime pay from their company? Based on the results of the research, the conclusion is obtained in the form of: The formulation of the problem discusses preventive and repressive legal protection for pregnant women workers who work overtime without overtime pay.